(untitled) (IUBAT Review, 2022)
The aim of the present study was to adapt a ‘Health-Specific Self-Efficacy Scales (HSSES)’ for use in Bangladesh. For this purpose, 155 respondents (age range 18 to 42 years) were selected using convenient sampling technique from different departments (students, facultiesand stuff) of IUBAT University. The scales were adapted following five steps such as ensuring construct equivalence, forward translation, focus group discussion, back translation as well as a pilot study. The findings demonstrated that the Bangla Version of ’Health-Specific Self-Efficacy Scales’ has sound reliability [Cronbach Alpha 0.79 (‘Nutrition Self-Efficacy (NSE)’ 0.84, ‘Physical Exercise Self-efficacy (PESE)’ 0.76,‘Alcohol Resistance Self-efficacy (ARSE)’ 0.82), Split-half reliability 0.73 (Spearman-Brown) and 0.76 (Guttman method), test-retest reliability 0.67] and satisfactory validity. These results exhibit that Health-Specific Self-Efficacy Scales (‘NSE’, ‘PESE’ and ‘ARSE’) are reliable and valid instruments for assessing nutrition, physical exercise and alcohol resistance-related self believes as well as health consciousness. Furthermore, this study uncovers the opportunity for further health-related research projects in Bangladesh. IUBAT Review—A Multidisciplinary Academic Journal, 5 (1): 15-25